Pengaruh kesadaran Wajib Pajak dan kualitas pelayanan pajak terhadap kepatuhan Wajib Pajak dalam membayar Pajak bumi dan Bangunan di kota Bandung - Rachmat Hidayat; Suci Rahma Wati (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of taxpayer awareness and tax service quality on taxpayer compliance in paying Land and Building Tax in Bandung City. The sampling technique used is simple random sampling with 75 respondents of Central Bandung City Taxpayers. The data of this study used primary data directly through questionnaires and analyzed using SPSS 25. The method of analysis of this study used multiple linear regression. The results showed that taxpayer awareness and tax service quality simultaneously had a significant effect on taxpayer compliance in paying Land and Building Tax, while the tax service quality partially had no effect on taxpayer compliance in paying Land and Building Tax.